Hadis Tentang Dilaknat Perempuan Yang Menolak Panggilan Suaminya - Muhammad Amin (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2019)
Hadith about the cursing of the woman who refused the call of her husband, seen from her sanad was considered valid by Imam Bukhari and Muslim, and Imam Tirmizi judged it by hasan sahih gharib. The meaning of the husband taking his wife to bed (firasy) is a figurative meaning. The real meaning is to invite to do jima. The meaning of the wife rejecting the husband's invitation is not fulfilled by the invitation of the husband to do jima 'without any age syar'i, such as fasting fardu and ihram. The intention of the husband is angry with his wife for not carrying out his obligations and giving him the rights of her husband One of the rights of the husband is in the wife's body that is channeling lust and having fun, If the rights of this husband are not fulfilled by the wife, then it brings God's anger, unless He bestows His forgiveness.